Influence of Quality, Procedures, and Service Facilities on Community Satisfaction with Hydrological Data Services at the Sulawesi II Gorontalo River Basin Center - Karundeng, Deby Rita; Suyanto, Mohamad Afan; Mokoagow, Arsin (PT. Riset Press International, 2024)
This research aims to determine and analyze the influence of service quality, service procedures and service facilities on community satisfaction with hydrological data services at the Sulawesi II Gorontalo River Regional Office. The multiple linear regression quantitative analysis model is used to analyze the influence of the independent variable on the dependent variable. The research results show that overall service quality, service procedures and service facilities influence public satisfaction, but for service quality the influence is not that significant. This shows that increasing community satisfaction is jointly influenced by service quality, service procedures and service facilities.